Sajak Sunda Periode 1949-1962 (Kajian Struktural dan Sosiologi Sastra) - Abidin, Zaenal; Koswara, Dedi (UPI, 2020)
Sundanese poetry of the period 1949-1962 was influenced by social events at that time, often the problems conveyed in poetry were irony, open, open, serious, satirical, and sentimental. Therefore, the aim of the research is to describe (1) the tone of the author, and (2) the fact of humanity that is reflected in his poems. This research is a qualitative research using analytic descriptive method. The technique of collecting data uses the study of documentation and contemporary author interviews. Poetry data was chosen 25 poems from 40 poems collected based on the year of publication, theme, and the poetry of the poem. The results of the study are based on the themes of the 1949-1962 Period poetry, namely (1) love for the motherland, (2) love for fellow human beings, (3) humanity, (4) mobs, (5) philosophical reflections, and (6) death. The tone analyzed in poetry includes formal attitudes in 11 poems, intimate attitudes in 11 poems, and arrogant attitudes in 3 poems. The conclusion of this study is the Sunda poem Period 1949-1962 raised about (1) love in the land of water / land Sunda, (2) love for fellow human beings, (3) humanity, philosophical contemplation, (3) hordes, (5) philosophical reflections, and (6) death.Â AbstrakSajak Sunda periode 1949-1962 dipengaruhi oleh kejadian sosial pada masa itu, seringkali masalah yang disampaikan dalam sajak yaitu ironi, terbuka, terbuka, serius, satir, dan sentimental. Oleh karena itu, tujuan dari penelitian adalah mendeskripsikan (1) tone/nada pengarang, dan (2) fakta kemanusiaan yang tergambar dalam sajak-sajaknya. Penelitian ini termasuk penelitian kualitatif yang menggunakan metode deskriptif analitik. Teknik mengumpulkan data menggunakan studi dokumentasi dan wawancara pengarang sezaman. Data sajak dipilih 25 sajak dari 40 sajak yang dikumpulkan berdasarkan pada tahun terbit, tema, dan titimangsa sajak. Hasil penelitian berdasarkan tema sajak Periode 1949-1962 yaitu (1) cinta tanah air, (2) cinta sesama manusa, (3) kemanusiaan, (4) gerombolan, (5) renungan falsafah, dan (6) kematian. Tone/nada yang dianalisis dalam sajak mecakup dalam sikap formal dalam 11 sajak, sikap intim dalam 11 sajak, dan sikap angkuh dalam 3 sajak. Kesimpulan dari penelitian ini adalah sajak Sunda Periode 1949-1962 mengangkat tentang (1) rasa cinta pada tanh air/tanah Sunda, (2) rasa cinta pada sesama manusia, (3) kemanusiaan, renungan falsafah, (3) Gerombolan, (5) renungan falsafah, dan (6) kematian.